(untitled) (American Journal of Technology and Applied Sciences, 2025)
In this article, the work carried out in the Republic of Uzbekistan today in terms of youth policy, coverage of young people with higher education, meaningful organization of their free time, ensuring their employment with a profession that fully meets the requirements of today’s modern era and world standards is analyzed, and the existing problems and shortcomings are studied.